2010
DOI: 10.1016/j.scitotenv.2010.09.041
|View full text |Cite
|
Sign up to set email alerts
|

A combined ecological and epidemiologic investigation of metal exposures amongst Indigenous peoples near the Marlin Mine in Western Guatemala

Abstract: In August 2009 a combined epidemiological and ecological pilot study was conducted to investigate allegations of human rights abuses in the form of exposures to toxic metals experienced by mine workers and Indigenous Mam Mayan near the Marlin Mine in Guatemala. In the human study there were no differences in blood and urine metals when comparing five mine workers with eighteen non-mine workers, and there were no discernible relationships between metals exposures and self-reported health measures in any study g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
(16 reference statements)
4
26
1
Order By: Relevance
“…Previous studies have demonstrated that concentrations of particulate matter and air pollutants are higher in areas closer to industrial facilities (Burstyn et al, 2007; Gildemeister et al, 2007). Therefore, our findings may support those of studies previously reporting associations between distance from point sources, duration and frequency of exposure to air pollutants, and subsequent higher body burden of toxicants for individuals living in those areas, including those reporting higher hair, urine, and blood levels of lead, mercury, and arsenic in those living closer to point sources such as agricultural land (Molina-Villalba et al, 2014), high-traffic roads (Ahamed et al, 2010; Gulson et al, 2006; Rahbar et al, 2002; Shen et al, 1997; Stroh et al, 2009), smelters (Do et al, 2011; Hegde et al, 2010; Hwang et al, 1997; Leroyer et al, 2000; Stroh et al, 2009), and mines (Basu et al, 2010; Wickre et al, 2004). Additionally, exposures to ambient air pollutants have been shown to stimulate oxidative stress and inflammation in humans, which may contribute to the pathogenesis of neurodevelopment and ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that concentrations of particulate matter and air pollutants are higher in areas closer to industrial facilities (Burstyn et al, 2007; Gildemeister et al, 2007). Therefore, our findings may support those of studies previously reporting associations between distance from point sources, duration and frequency of exposure to air pollutants, and subsequent higher body burden of toxicants for individuals living in those areas, including those reporting higher hair, urine, and blood levels of lead, mercury, and arsenic in those living closer to point sources such as agricultural land (Molina-Villalba et al, 2014), high-traffic roads (Ahamed et al, 2010; Gulson et al, 2006; Rahbar et al, 2002; Shen et al, 1997; Stroh et al, 2009), smelters (Do et al, 2011; Hegde et al, 2010; Hwang et al, 1997; Leroyer et al, 2000; Stroh et al, 2009), and mines (Basu et al, 2010; Wickre et al, 2004). Additionally, exposures to ambient air pollutants have been shown to stimulate oxidative stress and inflammation in humans, which may contribute to the pathogenesis of neurodevelopment and ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Urine was collected in sterile cups and samples were aliquot an hour after collection, frozen at -20 degrees Fahrenheit, and then moved to -70 degree Fahrenheit freezer for storage. The UCd was determined as previously described (Basu et al 2010; Srigboh et al 2016). Briefly, 0.5 mL of sample was digested with an equal volume of concentrated nitric acid and allowed to sit overnight in a fume hood.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 800 μL of urine or 4–9 mg of hair from the two cm closest to the scalp were analyzed according to methods we have previously described (Basu et al, 2010; Goodrich et al, 2011; Paruchuri et al, 2010). In every batch of 10–15 samples, one blank, one replicate sample, and a certified reference material (hair: NIES Japan CRM #13; urine: Institut National de Sante Publique Quebec standard QMEQAS08U-01; dogfish liver: DOLT4, National Research Council Canada) were included.…”
Section: Methodsmentioning
confidence: 99%